2020
DOI: 10.33457/ijhsrp.688181
|View full text |Cite
|
Sign up to set email alerts
|

Toward Organizational Evidence-Based Management in Healthcare Organizations

Abstract: To date, relatively little evidence has been published as to what represents effective evidencebased management in healthcare organizations. Existing studies are rarely conceived or developed with respect to organizational factors determining whether such studies succeed or fail. One of the challenges in linking organizational factors to evidence-based management is to identify the focus at which characteristics of healthcare organizations and management of knowledge resources are most obvious. This paper sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…Overfatigue will increase the risk of medical errors (Edú-Valsania et al, 2022;Maslach & Leiter, 2016). There is compelling evidence that burnout is linked to serious errors and even deaths (Alsaqqa & Akyürek, 2019). A metaanalysis of 47 studies involving more than 42,000 physicians found that physician burnout doubled the risk of adverse patient safety incidents and resulted in poorer overall quality of care and decreased patient satisfaction (Yates, 2020).…”
mentioning
confidence: 99%
“…Overfatigue will increase the risk of medical errors (Edú-Valsania et al, 2022;Maslach & Leiter, 2016). There is compelling evidence that burnout is linked to serious errors and even deaths (Alsaqqa & Akyürek, 2019). A metaanalysis of 47 studies involving more than 42,000 physicians found that physician burnout doubled the risk of adverse patient safety incidents and resulted in poorer overall quality of care and decreased patient satisfaction (Yates, 2020).…”
mentioning
confidence: 99%